2022
DOI: 10.3390/app12041899
|View full text |Cite
|
Sign up to set email alerts
|

High-Moment FeCo Magnetic Nanoparticles Obtained by Topochemical H2 Reduction of Co-Ferrites

Abstract: Cobalt ferrite nanoparticles of different stoichiometries synthesized by a sol–gel autocombustion method were used as a starting material to obtain high-moment Fe50Co50 and Fe66Co34 metal nanoparticles by topochemical hydrogen reduction. Structural and magnetic investigations confirmed the formation of FeCo nanoparticles with crystallite sizes of about 30 nm and magnetization at 0.5 T of ~265 Am2/kg (0 K), which was larger than the expected bulk value, likely because of the incorporation in the body-centered c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 47 publications
1
0
0
Order By: Relevance
“…The observed effect was explained by a change in the adsorption of hydrogen with a change in the spin structure of the magnetic particles. A similar effect was observed in the reduction of cobalt ferrite particles [29]. The results of both works correspond to the theoretical model of Melander et al [30], in which it is shown that the change in the electronic structure of nanoparticles significantly affects their interaction with hydrogen.…”
Section: Discussionsupporting
confidence: 86%
“…The observed effect was explained by a change in the adsorption of hydrogen with a change in the spin structure of the magnetic particles. A similar effect was observed in the reduction of cobalt ferrite particles [29]. The results of both works correspond to the theoretical model of Melander et al [30], in which it is shown that the change in the electronic structure of nanoparticles significantly affects their interaction with hydrogen.…”
Section: Discussionsupporting
confidence: 86%